2003
DOI: 10.1097/00005721-200311000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Adolescents’ Perspectives of Pregnancy

Abstract: Nurses caring for pregnant adolescents who have made the decision to keep their babies should carefully assess each individual's strengths, weaknesses, hopes, and goals prior to developing a plan of care. Identifying the teens' living situations and support from family, father of the baby, and/or friends and recognizing and building upon the strengths the teens bring to the pregnancy may influence the pregnancy's outcome. Encouraging attendance and participation in programs specifically designed for pregnant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…Adolescent mothers, therefore, have specific needs for help to successfully navigate through the combined demands of adolescent development and their role as a new parent. Researchers identify the significance of role identity, social support relationships, and developmental perspectives for the adolescent mother as she adapts to the demands of parenting (Clemmens, 2001(Clemmens, , 2003Gee & Rhodes, 2003;Rentschler, 2003). In addition, an adolescent's positive self-perception of parenting is influenced by having dependable social support relationships (Clemmens, 2003), feeling confident (Kretchmar & Jacobvitz, 2002), and being satisfied in her role as a mother (Secco, Atech, Woodgate, & Moffatt, 2002).…”
Section: Background Information Parenthood and Adolescent Mothersmentioning
confidence: 99%
“…Adolescent mothers, therefore, have specific needs for help to successfully navigate through the combined demands of adolescent development and their role as a new parent. Researchers identify the significance of role identity, social support relationships, and developmental perspectives for the adolescent mother as she adapts to the demands of parenting (Clemmens, 2001(Clemmens, , 2003Gee & Rhodes, 2003;Rentschler, 2003). In addition, an adolescent's positive self-perception of parenting is influenced by having dependable social support relationships (Clemmens, 2003), feeling confident (Kretchmar & Jacobvitz, 2002), and being satisfied in her role as a mother (Secco, Atech, Woodgate, & Moffatt, 2002).…”
Section: Background Information Parenthood and Adolescent Mothersmentioning
confidence: 99%
“…The adolescent's relationship with her mother may be the most powerful of the possible support systems available to her and may have the most influence on her ability to parent her newborn. Many adolescent mothers often live in their parental home due to financial constraints; thus, the adolescent's mother may be readily available to offer support (Gee & Rhodes, 2003;Rentschler, 2003).…”
Section: Social Support Education and The Adolescent Mothermentioning
confidence: 99%
“…These expectations may lead to the adolescent mother raising a difficult child because she was unprepared for the responsibility (Dallas et al, 2000). However, Rentschler (2003) found that motherhood may be a positive experience for some adolescent mothers. Having a baby improved their lives, and the experiences of being a mother helped them to feel more mature, self-reliant, and selfconfident (Spear, 2004).…”
Section: Adolescent Motherhood Developmentmentioning
confidence: 99%